Analysis of the relationship between the mutation site of the SLC39A4 gene and acrodermatitis enteropathica by reporting a rare Chinese twin: a case report and review of the literature - Wei Zhong; Chao Yang; Lei Zhu; Yu-Qi Huang; Yong-Feng Chen (BMC, 2020)
Abstract Background Acrodermatitis enteropathica (AE) is a rare autosomal recessive hereditary skin disease caused by mutations in the SLC39A4 gene and is characterized by periorificial dermatitis, alopecia and diarrhoea due to insufficient zinc absorption. Only one of the three known sets of twins with AE has genetic information. This case reports the discovery of new mutation sites in rare twin patients and draws some interesting conclusions by analysing the relationship between genetic information and clinical manifestations. Case presentation Here, we report a pair of 16-month-old twin boys with AE exhibiting periorificial and acral erythema, scales and blisters, while subsequent laboratory examination showed normal plasma zinc and alkaline phosphatase levels. Further Sanger sequencing demonstrated that the patients were compound heterozygous for two unreported SLC39A4 mutations: a missense mutation in exon 5 (c.926G > T), which led to a substitution of the 309th amino acid residue cysteine with phenylalanine, a splice site mutation occurring in the consensus donor site of intron 5 (c.976 + 2 T > A). A family study revealed that the boys' parents were heterozygous carriers of these two mutations. Conclusion We identified a new compound heterozygous mutation in Chinese twins with AE, which consisted of two previous unreported variants in exon 5 and intron 5 of SLC39A4. We propose an up-to-date review that different mutations in SLC39A4 may exhibit different AE manifestations. In conjunction with future research, our work may shed light on genotype-phenotype correlations in AE patients and provide knowledge for genetic counselling and treatment for AE patients.